Efficiency of acidemia correction on intermittent versus continuous hemodialysis in acute methanol poisoning. (7th February 2017) - Zakharov, Sergey; Pelclova, Daniela; Navratil, Tomas; Belacek, Jaromir; Latta, Jiri; Pisar, Michal; Rulisek, Jan; Leps, Jiri; Zidek, Pavel; Kucera, Cyril; Bocek, Robert; Mazur, Miroslav; et al.
Abstract: Context: Acidemia is a marker of prognosis in methanol poisoning, as well as compounding formate-induced cytotoxicity. Prompt correction of acidemia is a key treatment of methanol toxicity and methods to optimize this are poorly defined. Objective: We studied the efficiency of acidemia correction by intermittent hemodialysis (IHD) and continuous renal replacement therapy (CRRT) in a mass outbreak of methanol poisoning. Methods: The study was designed as observational cohort study. The mean time for an increase of 1 mmol/L HCO3 –, 0.01 unit arterial blood pH, and the total time for correction of HCO3 – were determined in IHD- and CRRT-treated patients. Results: Data were obtained from 18 patients treated with IHD and 13 patients treated with CRRT. At baseline, CRRT group was more acidemic than IHD group (mean arterial pH 6.79 ± 0.10 versus 7.05 ± 0.10; p  = 0.001). No association was found between the rate of acidemia correction and age, weight, serum methanol, lactate, formate, and glucose on admission. The time to HCO3 – correction correlated with arterial blood pH ( r = −0.511; p  = 0.003) and creatinine ( r  = 0.415; p  = 0.020). There was association between the time to HCO3 – correction and dialysate/effluent and blood flow rates ( r = −0.738; p  < 0.001 and r = −0.602; p  < 0.001, correspondingly). The mean time for HCO3 – to increase by 1 mmol/L was 12 ± 2 min for IHD versus 34 ± 8 min for CRRT ( p  < 0.001), and the mean time for arterial blood pH to increase 0.01 was 7 ± 1 mins for IHD versus 11 ± 4 min for CRRT ( p  = 0.024). The mean increase in HCO3 – was 5.67 ± 0.90 mmol/L/h for IHD versus 2.17 ± 0.74 mmol/L/h for CRRT ( p  < 0.001). Conclusions: Our study supports the superiority of IHD over CRRT in terms of the rate of acidemia correction.